Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/antibiotics12040727
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Inappropriate Use of Antibiotics in Infants under 3 Years of Age in Primary Care: A Qualitative Study of the Paediatricians’ Perceptions

Abstract: Antibiotic consumption in infants of less than three years is higher than average the average consumption for general population. The aim of this study was to explore paediatricians’ opinions regarding factors influencing inappropriate use of antibiotics in early infancy in primary care. A qualitative study based on the grounded theory using convenience sampling was conducted in Murcia Region, Spain. Three focal discussion groups were developed with 25 participants from 9 health areas (HA) of Murcia Region. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…The socio-economic determinants identified in this study align with previous research. Education emerged as a significant factor influencing KAP, consistent with findings from various studies conducted in different settings [ [38] , [39] , [40] ]. This highlights the crucial role of education in improving knowledge, attitudes, and practices related to antibiotics use and AMR.…”
Section: Discussionsupporting
confidence: 86%
“…The socio-economic determinants identified in this study align with previous research. Education emerged as a significant factor influencing KAP, consistent with findings from various studies conducted in different settings [ [38] , [39] , [40] ]. This highlights the crucial role of education in improving knowledge, attitudes, and practices related to antibiotics use and AMR.…”
Section: Discussionsupporting
confidence: 86%
“…The prescribing physicians are also influenced by a high workload in consultations, family pressure for antibiotic prescription, parental anxiety, insecurity of non-prescription, fear of losing patients, and insufficient knowledge [17,30,31]. In a previous qualitative study of our group, the misuse of antibiotics by pediatricians was also associated with poor knowledge and limited use of clinical practice guidelines [17].…”
Section: Discussionmentioning
confidence: 85%
“…Qualitative and quantitative studies have identified different factors associated with variability in antibiotic consumption, such as the prescription policies, the role of community pharmacies in dispensing antibiotic agents without prescriptions, the pharmaceutical market, the economic and sociocultural factors, the management models of healthcare systems, and the prescribing physicians themselves [11,28]. The prescribing physicians are also influenced by a high workload in consultations, family pressure for antibiotic prescription, parental anxiety, insecurity of non-prescription, fear of losing patients, and insufficient knowledge [17,30,31]. In a previous qualitative study of our group, the misuse of antibiotics by pediatricians was also associated with poor knowledge and limited use of clinical practice guidelines [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations